Span-wise coherence of fluctuating forces on twin bridge decks and the turbulence effect. Issue 15 (November 2019) - Xia, Jinlin; Li, Ke; Ge, Yaojun
Unlike the adequate researches on a single-box girder, the understanding of span-wise force correlation on twin decks is limited. A sectional model pressure testing of a widely slotted twin-box girder has been carried out in the background of a 5000-m-long bridge. Three grid configurations separated the effect of turbulence intensity and integral scale. Seven test sections were set on the model with totally 532 pressure taps. After the correction of pressure distortion, the correlation coefficients and integral scales of forces were compared on the leeward and the windward decks. Root coherence of lift was analyzed in detail at several separation distances. Pressure signals were used to explain why force coherence is stronger than flow and why "low frequency curve" phenomenon occurs. Considering the shortage of existing expressions, a simple but efficient form was proposed which can fit the coherence on the leeward, the windward, and the whole decks. The parameters in different flows can be reconstructed by linear functions which benefits new model's application. In the final, the influences of turbulence intensity and integral scale on force coherence were illustrated.